Proximal Junctional Kyphosis or Failure After Adult Spinal Deformity Surgery - Review of Risk Factors and Its Prevention - Lee, Byung-Jou; Bae, Sung Soo; Choi, Ho Young; Park, Jin Hoon; Hyun, Seung-Jae; Jo, Dae Jean; Cho, Yongjae (Neurospine, 2023)
Proximal junction kyphosis (PJK) is a common imaging finding after long-level fusion, and proximal junctional failure (PJF) is an aggravated form of the progressive disease spectrum of PJK. This includes vertebral fracture of upper instrumented vertebra (UIV) or UIV+1, instability between UIV and UIV+1, neurological deterioration requiring surgery. Many studies have reported on PJK and PJF after long segment instrumentation for adult spinal deformity (ASD). In particular, for spine deformity surgeons, risk factors and prevention strategies of PJK and PJF are very important to minimize reoperation. Therefore, this review aims to help reduce the occurrence of PJK and PJF by updating the latest contents of PJK and PJF by 2023, focusing on the risk factors and prevention strategies of PJK and PJF. We conducted a search on multiple database for articles published until February 2023 using the search keywords “proximal junctional kyphosis,” “proximal junctional failure,” “proximal junctional disease,” and “adult spinal deformity.” Finally, 103 papers were included in this study. Numerous factors have been suggested as potential risks for the development of PJK and PJF, including a high body mass index, inadequate postoperative sagittal balance and overcorrection, advanced age, pelvic instrumentation, and osteoporosis. Recently, with the increasing elderly population, sarcopenia has been emphasized. The quality and quantity of muscle in the surgical site have been suggested as new risk factor. Therefore, spine surgeon should understand the pathophysiology of PJK and PJF, as well as individual risk factors, in order to develop appropriate prevention strategies for each patient.